ON THE PROBLEM OF TORE DIFFEOMORPHISM EXTENSION AND ITS APPLICATIONS - A. M. Lukatsky (Научный вестник МГТУ ГА, 2016)
The construction of the extensions of a 2-torus diffeomorphism up to volume preserving diffeomorphism of solid tori is proposed. The construction is illustrated on the example of extension of diffeomorphism of action on the torus. These extensions are used for the construction of kinematic dynamo examples onto solid torus. For the case of n -sphere a generation of results obtained before is proposed.